Translating Political Metaphors: Conflict Potential of zenci [negro] in Turkish-English - Bulut, Alev (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
Political metaphors are expressed by lexical items with political content. Their transfer into other languages as part of political texts involves a potential of conflict due to their political and ideological load. Political interviews that are published through interpretation may be used to exemplify how transfer of source metaphors involve conflict depending on the translational decisions. This article focuses on the transfer of a political metaphor in an interpreter-mediated political interview as a source of potential conflict. The article first presents the concept of ideology in translation and markers of ideology in relation to political correctness and conflict as ideological aspects of political translation. It then focuses on zenci [negro/nigger] in Turkish as a political metaphor in transfer into English. The background for and the analysis of the sample metaphor in source and target languages, as well as the conclusions driven out of this case, aim to set the grounds for future discussions of similar cases in Turkish-English political translation.